Pengaruh Motivasi dan Literasi Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Peserta PMW Untag Surabaya - Desi Ramadhani; Awin Mulyati; Diana Juni Mulyati (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to determine whether there is an influence of Motivation (X1) and Entrepreneurial Literacy (X2) on Entrepreneurial Interest (Y) in Students Participating in PMW Untag Surabaya. With the large number of unemployment problems, the Entrepreneurial Student Program is needed to improve entrepreneurial skills among students, so that it is hoped that it can encourage students to start and develop their businesses. This research has the title "The Influence of Entrepreneurial Motivation and Literacy on Entrepreneurial Interest in Students Participating in PMW Untag Surabaya" using a quantitative approach. Data was collected through questionnaires distributed to 65 students participating in PMW Untag Surabaya. The sampling technique used is a saturated sampling technique which is included in the type of non-probability sampling. The research results show that the Motivation variable and the Entrepreneurial Literacy variable have a simultaneous influence on Entrepreneurial Interest. However, partially the Motivation variable has no influence on the Entrepreneurial Interest variable, this is because some students who participate in PMW are not motivated for the reason that some students take part in PMW only to get conversion grades in several courses. Therefore, it is recommended that universities pay more attention to programs that can increase entrepreneurial motivation and literacy towards entrepreneurial interests, such as holding regular training, provisioning or socialization activities related to entrepreneurship.